Understanding the Role of Communication in Promoting Active and Activist Citizenship. Issue 9 (September 2014) - Hammett, Daniel
Abstract State and nation‐building practices are central to governments around the world. The definition of citizenship – of who does and does not belong, and the rights, obligations and practices associated with being a citizen – is at the crux of these concerns. This article considers what is meant by citizenship and explores the ways in which government ideals of the 'active' citizen are negotiated and translated by citizens in everyday life, often resulting in the emergence of the 'activist' citizen. Particular attention is paid to the ways in which the idea(l)s of citizenship are communicated and contested, not only by governments through citizenship education and citizenship tests but also by civil society and citizens who draw upon multiple influences to contest and makes claims to citizenship in ways that disrupt government ideas of 'good citizenship'. Of growing concern to these negotiations are the ways in which multiple stakeholders use new technologies and social media to in engage in, and mobilise around, debates about values, meanings and practices of citizenship.